Object-oriented analysis of the numerical modelling of castings solidification - Sczygiol, Norbert (Computer Assisted Methods in Engineering and Science, 2001)
The paper concerns a method of implementation for the numerical modelling of the solidification process in which the finite element method was used. Modern techniques of software engineering were applied to reach the aim. The decomposition of the problem domain, for the needs of object-oriented analysis, was carried out. The relationships between parts of the analysed problem were discussed. At first , the object-oriented analysis was investigated in general for the wide range of problems solved by the finite element method, e.g. thermomechanic problems of castings, and then it was investigated in detail for the solidification process. The most important specialisation of classes for object implementation of the solidification model were also discussed. The enthalpy solidification formulations were used in the numerical modelling. The three models of solid phase growth, used for solidification modelling of two-component alloys, were described. The method for determining the dependence of enthalpy in relation to temperature and the formula for calculating the solid fraction were shown for each of the three models.